2019
DOI: 10.7554/elife.43561
|View full text |Cite
|
Sign up to set email alerts
|

Human VPS13A is associated with multiple organelles and influences mitochondrial morphology and lipid droplet motility

Abstract: The VPS13A gene is associated with the neurodegenerative disorder Chorea Acanthocytosis. It is unknown what the consequences are of impaired function of VPS13A at the subcellular level. We demonstrate that VPS13A is a peripheral membrane protein, associated with mitochondria, the endoplasmic reticulum and lipid droplets. VPS13A is localized at sites where the endoplasmic reticulum and mitochondria are in close contact. VPS13A interacts with the ER residing protein VAP-A via its FFAT domain. Interaction with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 92 publications
5
155
0
1
Order By: Relevance
“…Major advances in understanding the pathomechanism of ChAc and the function of chorein and its orthologues have been made recently [7][8][9][10]25]. Still, the main focus of the scientific community lies on the investigation of erythrocyte and medium spiny neuron (MSN) phenotypes as the primarily affected cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major advances in understanding the pathomechanism of ChAc and the function of chorein and its orthologues have been made recently [7][8][9][10]25]. Still, the main focus of the scientific community lies on the investigation of erythrocyte and medium spiny neuron (MSN) phenotypes as the primarily affected cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work on these functional aspects was conducted in yeast, where vacuole sorting, sporulation and inter organelle signaling was described [5,6]. More recently, further functional aspects of VPS13A were revealed by description of its function as a lipid transport protein, where it is located at various membrane contact sites-most notably the endoplasmic reticulum and mitochondria [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial function (Tasseva et al, 2013) and balanced fusion and fission (Steenbergen et al, 2005) are dependent on specific lipid composition, and therefore, lipid exchange at ER-mitochondria MCSs may be critical in regulating these processes. The Vps13 family of lipid-transfer proteins are localized to a variety of intracellular membrane contacts; of these, Vps13A (vacuolar protein sorting-associated protein 13A), which directly interacts with VAPA (Yeshaw et al, 2019), is found at mammalian ER-mitochondrial MCSs (Kumar N. et al, 2018), although it is not known how much it contributes to lipid transport there (Petrungaro and Kornmann, 2019). Oxysterol binding protein (Osbp)-related proteins ORP5 and ORP8 are also found at ER-mitochondria MCS, where they mediate non-vesicular transport of phosphatidylserine from the ER to mitochondria in mammalian cells (Rochin et al, 2019).…”
Section: Er-mitochondria Mcsmentioning
confidence: 99%
“…Molecules identified at these tethers include a complex formed by diacylglycerol O-acyltransferase 2 (DGAT2) (in LD membrane) and the fatty acid transport protein FATP1 (in ER membrane) (Xu et al, 2012); one formed by LD-associated Rab18 with the ER-associated proteins NAG-RINT1-ZW10 (NRZ complex) and Syntaxin18, Use1 and BNIP1 (SNARE proteins) (Xu et al, 2018); and tethering mediated by Vps13A and Vps13C (Kumar N. et al, 2018). At least one of them, Vps13A, interacts with the ERmembrane protein VAP-A (Yeshaw et al, 2019). These tethers, which are involved in LD biogenesis, have not been reported in neurons yet.…”
Section: Er Mcs and Intracellular Membrane Traffickingmentioning
confidence: 99%
“…The VPS13 protein family is comprised of four closely-related proteins, VPS13A-D (29). VPS13 family proteins are localized at various inter-organelle membrane contact sites and facilitates non-vesicular lipid transport (30,31). Interestingly, mutations VPS13D are associated with recessive ataxia (32).…”
Section: Genetic Screen To Identify Cellular Factors That Control Primentioning
confidence: 99%